Barron's MAT : Miller Analogies Test - Sternberg, Robert J; Sternberg, Karin; Barron's Educational Series, Inc. (Hauppage, New York : Barron's Educational Series, Inc., 2009)
"This updated manual prepares prospective test takers for success on the MAT, a timed word-association test that is widely used to screen applicants to graduate level academic programs. The MAT is also used as a placement exam for management positions in many businesses. The book's main features include: One diagnostic test and eleven full-length practice exams; Self-scoring answer keys following each test; Approximately 1,500 additional practice questions with answers; Advice to help test takers solve analogy problems. Helpful brush-up check lists cover graduate level vocabulary with brief word definitions, selected foreign words and phrases used in English with their meanings, and names of important persons in history, science, technology, and the arts that test-takers should be able to recognize. BONUS ONLINE PRACTICE TESTS: Students who purchase this book will also get FREE access to two additional full-length online MAT tests with all questions answered and explained."--Amazon.com.
Introduction. What this book can do for you ; How this book is organized ; Don't forget about the online tests! -- Part 1. Pretest. Answer key for the pretest ; Answer explanations for the pretest ; Pretest item classification chart -- Part 2. Achieving success on the Miller Analogies Test. Facts about the MAT ; A word on computer-based tests ; How to solve analogies ; Four ways of presenting analogies ; Practice in analogical thinking ; 30 helpful hints ; The 12 biggest mistakes test takers make ; Advice on preparing for the MAT ; Improving your intellectual skills -- Part 3. Kinds of analogies found on the Miller Analogies Test. Content of MAT analogies ; Practice in recognizing content areas ; Relationships used in MAT analogies ; The final word on classification -- Part 4. The Miller Analogies Test. Success of the MAT as a measuring instrument -- Part 5. Review for the Miller Analogies Test. What this review contains ; Vocabulary ; Special collective nouns ; -ology words ; Word demons ; Selected foreign words and phrases used in English ; Alphabets and their characteristics ; Geography ; History ; Social sciences ; Art and architecture ; Literary forms and figures ; Music ; Science ; Animal names ; Mythology -- Part 6.MAT practice tests. Practice test 1 ; Practice test 2 ; Practice test 3 ; Practice test 4 ; Practice test 5 ; Practice test 6 ; Practice test 7 ; Practice test 8 ; Practice test 9 ; Practice test 10 ; Practice test 11.
"Updated for the computer-based test"--Cover.
Keywords: Miller analogies test -- Study guides; Universities and colleges -- United States -- Graduate work -- Entrance examinations -- Study guides